RANCANG BANGUN SISTEM MONITORING THERMAL OVERLOAD RELAY PADA MOTOR INDUKSI 3 PHASA - Mispan, Mispan; Adam, Ahamd Antares; Amin, Nurhani; Pirade, Yulius S. (Foristek, 2023)
Thermal Overload Relay (TOR) is a tool that works based on heat (temperature) where the flowing current will be converted into heat to affect the bimetal. The length of trip time on the Thermal Overload Relay (TOR) varies depending on the setting value and the magnitude of the load current flowing. This prompted researchers to conduct trials and analyze Thermal Overload Relay (TOR). The research to be carried out here is to conduct a Thermal Overload Relay (TOR) test by adjusting the setting value and giving it more load, then analyzing whether the setting value works according to the setting value. When the motor is loaded, by holding the motor shaft, nothing happens or does not work on thermal overload, because the setting on the thermal overload relay is 2.5 A while the current obtained when the motor shaft is held is 0.40 A